An analysis of information technology taxonomy literature towards managing knowledge - Jarjis, Junaiza (2008)
Taxonomy is a method used to ease information retrieval for an effective knowledge management system.Studies have found information technology is vital for knowledge to be successfully managed and shared. We decided therefore to survey IT taxonomy studies using literature review and classification of articles from 1989 to 2008 in order to explore how taxonomy applications have developed in this period.Based on 62 articles found, the study classifies the taxonomy research into main topics and scope, methodologies most often applied, theories and models, and contributing countries. Based on the findings, we offer suggestions on improving research in this field.